Update of occurrence and hunting yield‐based data models for wild boar at European scale: new approach to handle the bioregion effect. Issue 5 (26th May 2020) - ,; Acevedo, Pelayo; Croft, Simon; Smith, Graham; Blanco‐Aguiar, Jose Antonio; Fernández‐López, Javier; Scandura, Massimo; Apollonio, Marco; Ferroglio, Ezio; Keuling, Oliver; Sange, Marie; Zanet, Stefania; et al.
Abstract : The ENETWILD consortium updated in August 2019 suitability maps of wild boar occurrence and relative abundance based on hunting statistics, providing predictions at 10x10 km. External validation of this relative abundance model and a new downscaling on a 2x2 km grid was addressed in the ENETWILD report in January 2020. In this report, we update and incorporate additional data to provide new maps of wild boar suitability with a resolution of 2x2 km, obtained from a presence‐only algorithm, and a new model based on hunting yield data for MS and neighbouring countries. Hunting yield‐based modelling provides further novelties in two ways: new predictor variables and new (two) modelling approaches, i.e. smooth bioregion modelling and two‐step independent bioregion modelling). Internal validations and comparisons among previous and new suitability and hunting yield models were also addressed, as well as external evaluation of the best new approach at European scale (at country level). The suitability map showed a good agreement with the expert‐derived species range published by the International Union for Conservation of Nature. New models of relative abundance performed in general better than the previous one according to internal validations, concretely the two‐step independent bioregion approach gives the best validation scores. This approach solved the abrupt changes in predictions between bioregion boundaries. As with the previous model, the external evaluation of the new model based on hunting yield presented certain over‐prediction of the total hunting bags reported per country, although a high linearity between observed and predicted values was achieved. Previous and new hunting yield model predictions showed disagreements particularly in North and East regions, and other scattered areas in South and West, being areas in which the new model provides more reliable predictions. Hunting yield model outputs showed a relevant improvement in smoothing transitions between bioregions due to the flexibility provided by the new approach. Our analysis showed only partial agreement between suitability and relative abundance models, and reasons for these differences are discussed in this report.